Mixed solvent for preparing glue solution for halogen-free antimony-free flame-retardant laminated board, glue solution, prepreg and laminated board
By using a specific mixed solvent system to prepare the glue solution of halogen-free antimony-free flame-retardant laminate, the problems of high DMF content and poor overall performance of the laminate are solved, and the DMF content is less than 3000ppm and high performance are achieved.
Patent Information
- Application Number
- CN202510251200.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-04
- Publication Date
- 2025-04-25
AI Technical Summary
The existing laminates have either high DMF content or poor overall performance, which is difficult to meet the limitations and high performance requirements of REACH regulations on the residual DMF.
A mixed solvent system is adopted, including mixed solvent 1 and mixed solvent 2, and the gum solution for halogen-free antimony-free flame retardant laminate is prepared by combining N,N-dimethylformamide, ethanol, dimethylsulfoxide, gamma-butyrolactone and propylene glycol methyl ether, ethyl acetate, isopropanol and other components in a specific mass ratio.
The DMF content of the laminate is less than 3000ppm, and has comprehensive properties such as high thermal conductivity, high CTI, excellent flame retardancy, halogen-free and antimony-free, which meets the requirements of REACH regulations.
Smart Images

Figure SMS_4 
Figure SMS_6 
Figure SMS_7
Abstract
Description
Technical Field
[0001] The invention relates to a mixed solvent for preparing an adhesive for a halogen-free and antimony-free flame-retardant laminate, an adhesive, a prepreg and a laminate. Background Art
[0002] In the field of electronics and electrical, as products develop rapidly towards miniaturization, high performance and high reliability, the requirements for basic materials such as laminates are becoming increasingly stringent.
[0003] Traditional laminates CEM-3 or FR-4 are widely used. The raw materials used to prepare the glue for laminates generally include resins, curing agents, curing accelerators and other substances. These raw materials are usually dissolved in DMF (N,N-dimethylformamide). DMF has excellent solubility and stable performance and is a widely used solvent. However, DMF is a low-toxic chemical. Long-term exposure may increase the risk of malignant tumors such as lung cancer and nasopharyngeal cancer.
[0004] Therefore, from December 12, 2023, REACH regulations (EU regulations on preventive management of all chemicals entering its market) require that the residual DMF in copper clad laminate products is less than 3000ppm.
[0005] Therefore, how to provide a copper clad laminate with a DMF content of less than 3000 ppm and excellent comprehensive performance is a technical problem to be solved urgently in this field. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the defects of the prior art laminates that either the DMF content is high or the comprehensive performance is poor, and to provide a mixed solvent, adhesive, prepreg, and laminate for preparing adhesive for halogen-free and antimony-free flame-retardant laminates.
[0007] By using the mixed solvent of the present invention to prepare the glue for laminated boards, the DMF content of the laminated boards (such as copper clad boards) can be less than 3000ppm. At the same time, the laminated boards have excellent comprehensive properties, such as TG ≥ 155°C, high thermal conductivity, high CTI, excellent flame retardancy, halogen-free and antimony-free, etc.
[0008] The present invention provides a mixed solvent for preparing a glue solution for a halogen-free and antimony-free flame-retardant laminate, wherein the mixed solvent comprises a mixed solvent 1 and a mixed solvent 2; wherein:
[0009] The mixed solvent 1 comprises: N,N-dimethylformamide, ethanol, dimethyl sulfoxide, and γ-butyrolactone, and the mass ratio of the N,N-dimethylformamide, the ethanol, the dimethyl sulfoxide, and the γ-butyrolactone is (4-6): (2-4): 1:1;
[0010] The mixed solvent 2 comprises: propylene glycol methyl ether, ethyl acetate, and isopropanol, and the mass ratio of the propylene glycol methyl ether, the ethyl acetate, and the isopropanol is (4-6): (2-4):2.
[0011] In the present invention, N,N-dimethylformamide (DMF) is an organic compound with a chemical formula of C 3 H 7 NO is a colorless, transparent liquid and is an excellent solvent with a wide range of uses.
[0012] In the present invention, ethanol (ETOH), referred to as ETOH, is a kind of alcohol compound, and its chemical formula is C 2 H 6 O.
[0013] In the present invention, dimethyl sulfoxide (DMSO) is a sulfur-containing organic compound with a molecular formula of C 2 H6OS.
[0014] In the present invention, γ-butyrolactone (1,4-Butyrolactone), referred to as GBL, is an organic compound with a chemical formula of C 4 H 6 O 2 .
[0015] In the present invention, propylene glycol monomethyl ether (PM) is a diol ether solvent with a molecular formula of CH 3 CHOHCH 2 OCH 3 .
[0016] In the present invention, ethyl acetate, referred to as EA, is an organic compound with a chemical formula of C 4 H 8 O 2 .
[0017] In the present invention, isopropanol (IPA), also known as 2-propanol, is a secondary alcohol with a molecular formula of C 3 H 8 O.
[0018] In some preferred embodiments of the present invention, in the mixed solvent 1, the mass ratio of the N,N-dimethylformamide, the ethanol, the dimethyl sulfoxide, and the γ-butyrolactone is 5:3:1:1.
[0019] In some preferred embodiments of the present invention, in the mixed solvent 2, the mass ratio of the propylene glycol methyl ether, the ethyl acetate, and the isopropanol is 5:3:2.
[0020] In some embodiments of the present invention, the mass fraction of the mixed solvent 1 is 450-550 parts, for example, 500 parts.
[0021] In some embodiments of the present invention, the mass fraction of the mixed solvent 2 is 135-165 parts, for example, 150 parts.
[0022] In some embodiments of the present invention, the mass fraction of the mixed solvent 2 is 765-935 parts, for example, 850 parts.
[0023] The DMF content in the laminated board prepared by using the mixed solvent of the present invention can be less than 1000 ppm, and the DMF content can also be less than 800 ppm or 500 ppm.
[0024] The present invention also provides a method for preparing a halogen-free and antimony-free flame-retardant adhesive for laminated boards. The raw materials of the adhesive include the following components in parts by mass:
[0025] Resin, curing agent, curing accelerator, silane coupling agent, and the mixed solvent;
[0026] Optionally, the raw material further comprises an inorganic filler;
[0027] The preparation method of the adhesive for the halogen-free and antimony-free flame-retardant laminate comprises the following steps:
[0028] (1) mixing the mixed solvent 1, the curing agent, the curing accelerator and part of the inorganic filler in the mixed solvent, and stirring to obtain a mixture A;
[0029] (2) mixing the mixture A with the silane coupling agent, the resin, and the mixed solvent 2 in the mixed solvent, and stirring to obtain a mixture B;
[0030] (3) Under stirring conditions, the mixture B and the remaining part of the inorganic filler are mixed, and sheared and ripened to obtain the halogen-free and antimony-free flame-retardant laminate adhesive.
[0031] In some embodiments of the present invention, the raw materials of the glue solution include the following component A:
[0032] (1) 360-440 parts of bisphenol A epoxy resin, wherein the bisphenol A epoxy resin has an epoxy equivalent of 185-190 g / eq and a viscosity of 12000-15000 mPa·s at 25° C.;
[0033] 1260-1540 parts of a DOPO type modified phosphorus-containing epoxy resin, wherein the DOPO type modified phosphorus-containing epoxy resin has an epoxy equivalent of 295-335 g / eq;
[0034] 180-220 parts of bisphenol A novolac epoxy resin, wherein the epoxy equivalent of the bisphenol A novolac epoxy resin is 190-220 g / eq;
[0035] 90-110 parts of a novolac epoxy resin, wherein the novolac epoxy resin has an epoxy equivalent of 176-181 g / eq;
[0036] 270-330 parts of bisphenol A type phosphorus-containing phenolic resin, wherein the viscosity of the bisphenol A type phosphorus-containing phenolic resin at 25° C. is 500-2500 mPa.s;
[0037] 90-110 parts of a tetrafunctional novolac epoxy resin, wherein the epoxy equivalent of the tetrafunctional novolac epoxy resin is 200-220 g / eq;
[0038] 450-550 parts of the mixed solvent 1, 135-165 parts of the mixed solvent 2;
[0039] 72-88 parts of curing agent;
[0040] 0.5-1.5 parts of curing accelerator;
[0041] 18-22 parts of silane coupling agent;
[0042] Optionally, the component A further comprises an inorganic filler.
[0043] In some embodiments of the present invention, the bisphenol A epoxy resin may be NPEL128E produced by Kunshan Nan Ya.
[0044] In some embodiments of the present invention, the solid content of the bisphenol A epoxy resin is 100%.
[0045] In some embodiments of the present invention, the mass fraction of the bisphenol A epoxy resin is 400 parts.
[0046] In some embodiments of the present invention, the DOPO-type modified phosphorus-containing epoxy resin may be DFE202 produced by Sichuan Dongcai.
[0047] In some embodiments of the present invention, the solid content of the DOPO-type modified phosphorus-containing epoxy resin is 70-80%, for example 75%.
[0048] In some embodiments of the present invention, the phosphorus content of the DOPO-type modified phosphorus-containing epoxy resin is 3.1-3.2%.
[0049] In some embodiments of the present invention, the mass fraction of the DOPO type modified phosphorus-containing epoxy resin is 1400 parts.
[0050] In some embodiments of the present invention, the bisphenol A novolac epoxy resin is SQAN-201EK80 produced by Shengquan.
[0051] In some embodiments of the present invention, the solid content of the bisphenol A novolac epoxy resin is 75-85%, for example 80%.
[0052] In some embodiments of the present invention, the mass fraction of the bisphenol A novolac epoxy resin is 200 parts.
[0053] In some embodiments of the present invention, the novolac epoxy resin may be DEN438 EK85J novolac epoxy resin produced by Dow.
[0054] In some embodiments of the present invention, the solid content of the phenolic epoxy resin is 80-90%, for example 85%.
[0055] In some embodiments of the present invention, the viscosity of the novolac epoxy resin at 25° C. is 600-1600 mPa.s.
[0056] In some embodiments of the present invention, the mass fraction of the phenolic epoxy resin is 100 parts.
[0057] In some embodiments of the present invention, the bisphenol A type phosphorus-containing phenolic resin is XZ92741 produced by Dow.
[0058] In some embodiments of the present invention, the solid content of the bisphenol A type phosphorus-containing phenolic resin is 56-58%.
[0059] In some embodiments of the present invention, the phosphorus content of the bisphenol A type phosphorus-containing phenolic resin is 9-10%.
[0060] In some embodiments of the present invention, the mass fraction of the bisphenol A type phosphorus-containing phenolic resin is 300 parts.
[0061] In some embodiments of the present invention, the tetrafunctional phenolic epoxy resin is NPPN431A70 produced by Kunshan Nan Ya.
[0062] In some embodiments of the present invention, the solid content of the tetrafunctional phenolic epoxy resin is 65-75%, for example 70%.
[0063] In some embodiments of the present invention, the softening point of the tetrafunctional novolac epoxy resin is 82-92°C.
[0064] In some embodiments of the present invention, the mass fraction of the tetrafunctional phenolic epoxy resin is 100 parts.
[0065] In some embodiments of the present invention, the mass ratio of the bisphenol A epoxy resin, the DOPO modified phosphorus-containing epoxy resin, the bisphenol A novolac epoxy resin, the novolac epoxy resin, the bisphenol A phosphorus-containing novolac resin, and the tetrafunctional novolac epoxy resin is 4:14:2:1:3:1.
[0066] In some embodiments of the present invention, the mass fraction of the curing agent is 80 parts.
[0067] In some embodiments of the present invention, the curing agent is DDS (4,4'-diaminodiphenyl sulfone) and / or DICY (dicyandiamide).
[0068] In some embodiments of the present invention, the mass fraction of DICY (dicyandiamide) is 45-55 parts, for example, 50 parts.
[0069] In some embodiments of the present invention, the mass fraction of the DDS (4,4'-diaminodiphenyl sulfone) is 27-33 parts, for example, 30 parts.
[0070] In some embodiments of the present invention, the mass ratio of the DICY to the DDS is 5:3.
[0071] In some embodiments of the present invention, the curing accelerator is diphenylimidazole.
[0072] In some embodiments of the present invention, the mass fraction of the curing accelerator is 0.9-1.1 parts, for example, 1.0 parts.
[0073] In some embodiments of the present invention, the silane coupling agent is KH-570, and its chemical name is γ-methacryloxypropyltrimethoxysilane.
[0074] In some embodiments of the present invention, the mass fraction of the silane coupling agent is 20 parts.
[0075] In some embodiments of the present invention, the inorganic filler includes graphene oxide.
[0076] Graphene oxide has certain flame retardant properties and can partially replace traditional flame retardants in halogen-free copper clad laminates, reducing the amount of flame retardants used, while improving the flame retardant and environmental performance of copper clad laminates; its flame retardant mechanism is mainly to form a carbon layer during the combustion process to prevent the transfer of heat and oxygen, thereby achieving the purpose of flame retardancy.
[0077] In some embodiments of the present invention, the mass fraction of the graphene oxide is 45-55 parts, for example, 50 parts.
[0078] In some embodiments of the present invention, the graphene oxide is a single layer.
[0079] In some embodiments of the present invention, the thickness of the graphene oxide is 0.8 nm-1.2 nm.
[0080] In some embodiments of the present invention, the specific surface area of the graphene oxide is 500m² / g-1000m² / g.
[0081] In some embodiments of the present invention, the carbon-oxygen ratio of the graphene oxide is between 2-4.
[0082] In some embodiments of the present invention, the inorganic filler further includes spherical aluminum oxide and / or aluminum hydroxide.
[0083] The aluminum hydroxide in the present invention can be used as a flame retardant to reduce the decomposition of the material surface and the formation of carbon particles, thereby significantly improving the flame retardancy of the material and reducing the thermal expansion coefficient and water absorption rate of the plate.
[0084] In the present invention, the spherical alumina can effectively improve the thermal conductivity of the copper-clad laminate, accelerate heat dissipation, and reduce its dielectric constant and thermal expansion coefficient.
[0085] In some embodiments of the present invention, the sum of the mass fractions of the spherical aluminum oxide and / or aluminum hydroxide is 1080-1320 parts, for example, 1200 parts.
[0086] In some embodiments of the present invention, the mass fraction of the aluminum hydroxide is 900-1100 parts, for example, 1000 parts.
[0087] In some embodiments of the present invention, the grade of the aluminum hydroxide is MARTINAL® OL-104LEO.
[0088] In some embodiments of the present invention, the purity of the aluminum hydroxide is ≥99.6%, and the whiteness is ≥93.
[0089] In some embodiments of the present invention, the particle size range of the aluminum hydroxide is: D50, 1.9±0.2 μm; D90, 3.2±1.0 μm.
[0090] In some embodiments of the present invention, the oil absorption rate of the aluminum hydroxide is 27-32 ml / 100g.
[0091] In some embodiments of the present invention, the conductivity of the aluminum hydroxide (10%, in water) is: 20 μS / cm.
[0092] In some embodiments of the present invention, the mass fraction of the spherical aluminum oxide is 180-220 parts, for example, 200 parts.
[0093] In some embodiments of the present invention, the grade of the spherical alumina is SLA-5.
[0094] In some embodiments of the present invention, the D50 particle size of the spherical alumina is 5±1 μm.
[0095] In some embodiments of the present invention, the D90 particle size of the spherical alumina is 15±3 μm.
[0096] In some embodiments of the present invention, the mass ratio of the spherical aluminum oxide to the aluminum hydroxide is 1:5.
[0097] In some embodiments of the present invention, the mass fraction of the inorganic filler is 1125-1375 parts, for example, 1250 parts.
[0098] In some embodiments of the present invention, the composition of component A is shown in the following table:
[0099] .
[0101] In some embodiments of the present invention, the method for preparing the adhesive for the halogen-free and antimony-free flame-retardant laminate comprises the following steps:
[0102] (1) mixing the mixed solvent 1 (added according to each component), the curing agent (added according to each component), the curing accelerator and part of the inorganic filler, and stirring for 10-12 hours to obtain a mixture A;
[0103] (2) Mixing the mixture A with the silane coupling agent, the resin (added according to each component), and the mixed solvent 2 (added according to each component), and stirring for 1-2 hours to obtain a mixture B;
[0104] (3) Under stirring conditions, the mixture B and the remaining part of the inorganic filler (added according to each component) are mixed, and shear-ripened for 4-5 hours at a speed of 2000-2200 rpm and a glue temperature of 40-60°C, and then shear-ripened for 6-7 hours at a speed of 900-1100 rpm and a glue temperature of 45-50°C (total aging time is about 10-12 hours), and finally the halogen-free and antimony-free flame-retardant laminate glue is obtained.
[0105] In some embodiments of the present invention, the raw materials of the glue solution include the following component B:
[0106] 540-660 parts of bisphenol A epoxy resin, wherein the bisphenol A epoxy resin has an epoxy equivalent of 185-190 g / eq and a viscosity of 12000-15000 mPa·s at 25° C.;
[0107] 900-1100 parts of DOPO type modified phosphorus-containing epoxy resin, wherein the epoxy equivalent of the DOPO type modified phosphorus-containing epoxy resin is 295-335 g / eq;
[0108] 360-440 parts of solid bisphenol A epoxy resin, wherein the solid bisphenol A epoxy resin has an epoxy equivalent of 840-900 g / eq and a melt viscosity of 6000-9000 mPa·s at 150° C.;
[0109] 180-220 parts of MDI modified epoxy resin, wherein the epoxy equivalent of the MDI modified epoxy resin is 250-310 g / eq; and,
[0110] 450-550 parts of a linear bisphenol A formaldehyde resin, wherein the linear bisphenol A formaldehyde resin has a hydroxyl equivalent of 120-124 g / eq;
[0111] 450-550 parts of the mixed solvent 1, 765-935 parts of the mixed solvent 2;
[0112] 72-88 parts of curing agent;
[0113] 0.9-1.1 parts of curing accelerator;
[0114] 18-22 parts of a silane coupling agent; and,
[0115] Inorganic filler.
[0116] In some embodiments of the present invention, the mass fraction of the bisphenol A epoxy resin is 600 parts.
[0117] In some embodiments of the present invention, the bisphenol A epoxy resin may be NPEL128E produced by Kunshan Nan Ya.
[0118] In some embodiments of the present invention, the solid content of the bisphenol A epoxy resin may be 100%.
[0119] In some embodiments of the present invention, the mass fraction of the DOPO type modified phosphorus-containing epoxy resin is 1000 parts.
[0120] In some embodiments of the present invention, the DOPO-type modified phosphorus-containing epoxy resin may be DFE202 produced by Sichuan Dongcai.
[0121] In some embodiments of the present invention, the solid content of the DOPO-type modified phosphorus-containing epoxy resin may be 75%.
[0122] In some embodiments of the present invention, the phosphorus content of the DOPO-type modified phosphorus-containing epoxy resin may be 3.1-3.2%.
[0123] In some embodiments of the present invention, the mass fraction of the solid bisphenol A epoxy resin is 400 parts.
[0124] In some embodiments of the present invention, the solid bisphenol A epoxy resin may be medium molecular weight NPES-904H produced by Kunshan Nan Ya.
[0125] In some embodiments of the present invention, the 25° C. softening point of the solid bisphenol A epoxy resin may be 100-112.
[0126] In some embodiments of the present invention, the density of the solid bisphenol A epoxy resin at 25°C may be 1.18 g / cm 3 .
[0127] In some embodiments of the present invention, the mass fraction of the MDI-modified epoxy resin is 200 parts.
[0128] In some embodiments of the present invention, the MDI modified epoxy resin may be DFE205 produced by Sichuan Dongcai.
[0129] In some embodiments of the present invention, the solid content of the MDI modified epoxy resin may be 75%.
[0130] In some embodiments of the present invention, the mass fraction of the linear bisphenol A formaldehyde resin is 500 parts.
[0131] In some embodiments of the present invention, the linear bisphenol A formaldehyde resin may be SH-2130 produced by Shengquan Group.
[0132] In some embodiments of the present invention, the free bisphenol A content of the linear bisphenol A formaldehyde resin may be 13-17%.
[0133] In some embodiments of the present invention, the softening point of the linear bisphenol A formaldehyde resin may be 127-132°C.
[0134] In some embodiments of the present invention, the electrical conductivity of the linear bisphenol A formaldehyde resin may be ≤20 μs / cm.
[0135] In some embodiments of the present invention, the resin composition in component B may be the following composition:
[0136] .
[0138] In the present invention, when the mixture A is observed under a polarizing microscope at 40 times (total magnification), there are less than 3 crystals of the curing agent (eg, DICY) in any field of view.
[0139] In some embodiments of the present invention, the stirring time in step (1) is 10-12 hours.
[0140] In some embodiments of the present invention, the stirring time in step (1) is 1-2 hours.
[0141] In some embodiments of the present invention, when the raw materials of the glue solution include the component A, the rotation speed of the shear ripening is 900-2200 rpm, such as 900-1100 rpm or 2000-2200 rpm.
[0142] In some embodiments of the present invention, when the raw materials of the glue solution include the component A, the shear aging temperature is 40-60°C, such as 45-50°C.
[0143] In some embodiments of the present invention, when the raw materials of the glue solution include the component A, the shear aging time is 10-12 hours.
[0144] In some embodiments of the present invention, when the raw materials of the glue solution include the component A, the shear ripening process is:
[0145] First, shear aging is performed at a speed of 2000-2200rpm and a glue temperature of 40-60℃ for 4-5 hours, and then shear aging is performed at a speed of 900-1100rpm and a glue temperature of 45-50℃ for 6-7 hours (the total aging time is about 10-12 hours).
[0146] In some embodiments of the present invention, when the raw materials of the glue solution include the component A, the gel time of the glue solution can reach 250-260 s.
[0147] In some embodiments of the present invention, when the raw materials of the glue solution include the component B, the rotation speed of the shear ripening is 900-1600 rpm, such as 900-1100 rpm or 1500-1600 rpm.
[0148] In some embodiments of the present invention, when the raw materials of the glue solution include the component B, the shear ripening temperature is 40-60°C, such as 45-50°C.
[0149] In some embodiments of the present invention, when the raw materials of the glue solution include the component B, the shear aging time is 18-22 hours.
[0150] In some embodiments of the present invention, when the raw materials of the glue solution include the component B, the shear ripening process is:
[0151] First, shear aging is performed at a speed of 1400-1600 rpm and a glue temperature of 40-50°C for 5-7 hours, and then shear aging is performed at a speed of 900-1100 rpm and a glue temperature of 40-50°C for 13-15 hours (the total aging time is about 18-22 hours).
[0152] In some embodiments of the present invention, when the raw materials of the glue solution include the component A, the mass fraction of the mixed solvent 2 is 135-165 parts, for example, 150 parts.
[0153] In some embodiments of the present invention, when the raw materials of the glue solution include the component B, the mass fraction of the mixed solvent 2 is 765-935 parts, for example, 850 parts.
[0154] The present invention also provides a glue solution for halogen-free and antimony-free flame-retardant laminated boards, which is prepared by the above-mentioned preparation method.
[0155] In some embodiments of the present invention, under the condition of a total aging time of 12 hours, the gel time of the glue solution can reach 250-260 s.
[0156] The present invention also provides a method for preparing a prepreg for a halogen-free and antimony-free flame-retardant laminate, which comprises the following steps: coating the adhesive on a reinforcing material, and drying to obtain the prepreg.
[0157] In the present invention, the reinforcing material may be electronic grade glass fiber cloth or electronic glass fiber felt.
[0158] In the present invention, the laminated board may be a FR-4 board or a CEM-3 board.
[0159] In the present invention, FR-4 can be generally divided into FR-4.0 (ordinary board) and FR-4.1 (halogen-free board).
[0160] In the present invention, the FR-4.1 board uses electronic grade glass fiber cloth, such as 7628, 2116, 1080, etc. as a reinforcing material.
[0161] In the present invention, the CEM-3 board uses electronic glass fiber felt, such as 75g, 105g, 150g, and 200g of electronic glass fiber felt as a reinforcing material.
[0162] The present invention also provides a prepreg for a halogen-free and antimony-free flame-retardant laminate, which is prepared by the method.
[0163] The present invention also provides a halogen-free antimony-free flame-retardant laminate, which comprises at least one prepreg for the halogen-free antimony-free flame-retardant laminate and a metal foil or a release film covering one or both sides of the laminated prepreg.
[0164] In some embodiments of the present invention, the metal foil is copper foil.
[0165] In some embodiments of the present invention, the metal foil clad laminate comprises, in sequence, a first copper foil layer, a semi-cured sheet whose reinforcing material is electronic grade glass cloth 2116, six semi-cured sheets whose reinforcing material is electronic grade glass cloth 7628, a semi-cured sheet whose reinforcing material is electronic grade glass cloth 2116, and a second copper foil layer.
[0166] In some embodiments of the present invention, the DMF content of the halogen-free and antimony-free flame-retardant laminate is less than 1000 PPM, such as less than 800 ppm or less than 500 ppm, and also such as 200 ppm.
[0167] The present invention also provides a method for preparing the halogen-free and antimony-free flame-retardant laminate, which comprises the following steps:
[0168] Lamination: Laminating a plurality of the halogen-free and antimony-free flame-retardant laminates with prepregs, and covering the upper and lower surfaces with metal foil or release film to obtain a semi-finished plate;
[0169] ② The semi-finished plate is subjected to hot pressing and vacuum pressing to obtain the semi-finished plate.
[0170] In the present invention, the preparation method of the semi-finished plate material can be: the semi-finished plate material is formed by a plurality of intermediate prepregs, upper and lower copper foils / release films, upper and lower steel plates, and 18 upper and lower kraft papers.
[0171] In the present invention, no pressure is required when stacking, and the stacking requirements generally follow the four major principles in this field: the principle of matching high and low glue content, the principle of consistent layout, the principle of structural symmetry, and the principle of left and right matching.
[0172] In the present invention, different electronic glass fiber cloths can be selected according to different thicknesses, such as 8 7628 electronic glass fiber cloth semi-cured sheets are used for 1.5mm thick plates; 2*7628+2*1506+2*7628 are used for 1.1mm thick plates; and 2*7628+1*2116+2*7628 are used for 0.9mm thick plates.
[0173] In step ②, the pressing method and conditions can be conventional methods and conditions in the art, such as hot pressing and vacuum segmented pressing. Ensure that the sheet is cooled gradually to avoid direct pressure release after hot pressing, which will cause large internal stress of the sheet, and increase cold pressing to reduce sheet warping.
[0174] In the present invention, the vacuum value of the hot-pressing vacuum pressing may be 750-800 mmHg, more preferably 760 mmHg.
[0175] In the present invention, the hot pressing and vacuum pressing can be carried out in stages, such as stage one, stage two, and stage three.
[0176] In the present invention, the first stage can be: under the condition of vacuum value of 740-750 mmHg; hot pressing temperature: 120-210°C, the temperature range represents a linear increase from 120°C to 210°C; hot pressing pressure: 5-25 kg / cm 2 , the pressure range is from 5 kg / cm 2 Linear pressure increase to 25 kg / cm 2 ; Hot pressing time: 55min; Heating and pressing are completed during the hot pressing process, the hot pressing temperature at the starting point of hot pressing is 120℃, and the hot pressing pressure is 5 kg / cm 2 The hot pressing temperature at the end of hot pressing is 210℃ and the hot pressing pressure is 25 kg / cm 2 .
[0177] In the present invention, the second stage can be: under the condition of vacuum value of 740-750 mmHg, hot pressing temperature: 210°C, hot pressing pressure is divided into initial pressure, intermediate pressure and late pressure, wherein: initial pressure is 25 kg / cm 2 The hot pressing time is 10 min, and the medium pressure is 35 kg / cm 2 The hot pressing time is 35 min, and the later pressure is 20 kg / cm 2 , Hot pressing time: 15min.
[0178] In the present invention, the third stage can be: under vacuum or non-vacuum conditions, hot pressing temperature: 210-120°C, the temperature range represents a linear temperature drop from 210°C to 120°C; hot pressing pressure: 20-30 kg / cm 2 , the pressure range is from 20kg / cm 2 Linear pressure increase to 30 kg / cm 2 ; Hot pressing time: 30min; Heating and pressing are completed during the hot pressing process, the hot pressing temperature at the starting point of hot pressing is 210℃, and the hot pressing pressure is 20 kg / cm 2 The hot pressing temperature at the end of hot pressing is 210℃ and the hot pressing pressure is 25 kg / cm 2 .
[0179] In the present invention, the term “comparative tracking index” (CTI) is referred to as CTI for short.
[0180] In the present invention, the term “glass transition temperature” (TG) is abbreviated as TG.
[0181] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0182] The reagents and raw materials used in the present invention are commercially available.
[0183] The positive and progressive effects of the present invention are:
[0184] 1. The mixed solvent in the present invention is excellent in solubility, safety, environmental protection and stability.
[0185] (1) Solubility
[0186] Broad spectrum solubility: The mixed solvent 1 system in the present invention can dissolve almost most common organic compounds, polymer materials and some inorganic compounds, and has a wider solubility range than a single traditional solvent. The mixed solvent 2 formed by the combination of propylene glycol methyl ether, ethyl acetate and isopropyl alcohol has a wider and more efficient solubility for various resins, additives, etc. in the production of halogen-free boards. Compared with some traditional single solvents or simple mixed solvents, it can better meet the requirements for dissolving and dispersing raw materials in the production of halogen-free boards.
[0187] Synergistic dissolution effect: The mixed solvent 1 in the present invention produces a synergistic effect, and has a stronger dissolving ability for some insoluble substances than when each is used alone. It can effectively reduce the surface tension of the solute, making the solute easier to disperse in the solvent and improving the dissolution efficiency. The mixed solvent 2 with a specific proportion can find a better dissolution balance between different types of resins and additives, which can not only ensure the good dissolution of the main resin components, but also make various functional additives evenly dispersed in the solution to form a stable system. The mixed solvent system formed by mixed solvent 1 and mixed solvent 2 helps to improve the performance consistency and stability of halogen-free boards.
[0188] (2) Security
[0189] Reduced toxicity risk: Although DMF and DMSO in the mixed solvent 1 are toxic to a certain extent, compared with some traditional highly toxic solvents such as benzene and chloroform, after mixing in this ratio, the overall amount of the mixed solvent 1 in the present invention may be reduced while achieving the same dissolving effect, thereby reducing the exposure risk of toxic substances. Moreover, ethanol is relatively low in toxicity and can dilute the toxicity of other solvents to a certain extent.
[0190] Improved flash point: Compared with some low-flash-point, flammable traditional solvents such as ether and acetone, the flash point of the mixed solvent 1 in the present invention is relatively high, and the risk of fire and explosion during use, storage and transportation is relatively low.
[0191] Low toxicity: Compared with some traditional organic solvents such as benzene, toluene, etc., the toxicity of propylene glycol methyl ether, ethyl acetate and isopropyl alcohol is relatively low. The use of mixed solvent 2 in the production process of halogen-free boards can reduce the risk of operators being exposed to highly toxic substances and reduce the harm to human health.
[0192] Enhanced non-flammability: Compared with some highly flammable traditional solvents, the flash point of mixed solvent 2 is relatively high, and the risk of fire and explosion during production, storage and transportation is relatively low, which improves the safety of the production process.
[0193] (3) Environmental protection
[0194] Improved biodegradability: ethanol is biodegradable and can be decomposed by microorganisms relatively quickly in the environment. The presence of ethanol in the mixed solvent 1 of the present invention makes the entire mixed solvent system more environmentally friendly to a certain extent than some traditional solvents that are difficult to degrade, and the pollution pressure on the environment is relatively small.
[0195] Reduced volatility: Compared with some volatile traditional solvents such as methanol, dichloromethane, etc., the volatility of the mixed solvent 1 in the present invention may be relatively low, which can reduce the solvent volatilization into the atmosphere to form organic waste gas, reduce the pollution to the atmospheric environment, and also help reduce the occurrence of environmental problems such as photochemical smog. After the mixed solvent 2 in the present invention is mixed with propylene glycol methyl ether, ethyl acetate, and isopropanol in a mass ratio of (4-6): (2-4): 2 (for example, 5:3:2), the overall volatilization rate is relatively moderate. Compared with some traditional solvents, it will not cause defects on the surface of the board, such as peeling, bubbles, etc., due to too fast volatilization, nor will it affect the production efficiency and the final performance of the board due to too slow volatilization, and can achieve good drying and curing effects during the production process.
[0196] Reduce volatilization loss: Reasonable volatilization rate makes the volatilization loss of solvent relatively small during the production process, which not only reduces production costs, but also reduces the pollution and safety hazards caused by the volatilization of solvents into the environment.
[0197] (4) Stability
[0198] Enhanced chemical stability: The components in the mixed solvent 1 system of the present invention interact with each other, which improves the chemical stability of the entire system. During storage and use, it is not easy to undergo chemical reactions such as decomposition and deterioration. It is more stable than some traditional solvents that are chemically active and easily react with other substances, and can better guarantee the performance and quality of the solution.
[0199] Better temperature adaptability: at different temperatures, the mixed solvent 1 in the present invention can maintain good performance, unlike some traditional solvents that are easy to solidify at low temperatures or easy to volatilize and decompose at high temperatures, and has a wider operating temperature range.
[0200] Cost advantage: Propylene glycol methyl ether, ethyl acetate and isopropyl alcohol are all large-scale industrially produced chemical products with relatively stable supply and relatively reasonable prices. By mixing them in a reasonable proportion, while meeting the production requirements of halogen-free boards, the production cost can be reduced. Compared with some expensive special solvents or imported solvents, they have obvious cost advantages.
[0201] Supply stability: The production technology of the solvent types involved in the mixed solvent of the present invention is mature, the market supply is sufficient, and the impact of raw material supply and market fluctuations is relatively small, which can ensure the stable supply of halogen-free board manufacturers and reduce the risk of production interruption due to solvent shortage.
[0202] 2. The flame-retardant laminate (FR-4.1 or CEM-3) with high thermal conductivity, CTI ≥ 600 V, TG ≥ 155°C, halogen-free and antimony-free prepared by the mixed solvent of the present invention meets the production process requirements of the downstream printed circuit board (PCB) for the board, and the DMF content of the prepared board can be less than 1000ppm, or even less than 800ppm or 500ppm. In addition, the board has good comprehensive performance, especially halogen-free, thermal conductivity, CTI, flame retardant, TG, and thickness uniformity. For example, the bromine content (ppm) is less than 500ppm, which is far lower than the industry standard value (bromine content <900ppm); the thermal conductivity is high, and there is no delamination or blistering in the thermal stress test. DETAILED DESCRIPTION
[0203] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0204] In the following examples and comparative examples, the sources and descriptions of the raw materials are as follows:
[0205] DMF: N,N-dimethylformamide;
[0206] ETOH: ethanol;
[0207] DMSO: dimethyl sulfoxide;
[0208] GBL: gamma-butyrolactone;
[0209] DICY: dicyandiamide;
[0210] DDS: 4,4'-diaminodiphenyl sulfone;
[0211] Diphenylimidazole: 2-Phenylimidazole;
[0212] Graphene oxide: thickness is 0.8nm-1.2nm, single layer, specific surface area is 500m² / g-1000m² / g, carbon-oxygen ratio is between 2-4;
[0213] Silane coupling agent KH-570: γ-methacryloxypropyltrimethoxysilane;
[0214] Bisphenol A epoxy resin: NPEL128E produced by Kunshan Nan Ya, solid content 100%, epoxy equivalent 185-190g / eq, viscosity 12000-15000mPa·s at 25°C;
[0215] DOPO-type modified phosphorus-containing epoxy resin: DFE202 produced by Sichuan Dongcai, with a solid content of 75%, epoxy equivalent of 295-335g / eq, and a phosphorus content of 3.1-3.2%;
[0216] Bisphenol A novolac epoxy resin: SQAN-201EK80 produced by Shengquan, solid content 80%, epoxy equivalent 190-220g / eq;
[0217] Phenolic epoxy resin: DEN438 EK85J produced by Dow, solid content 85%, viscosity 600-1600 mPa.s / 25℃, epoxy equivalent 176-181g / eq;
[0218] Bisphenol A type phosphorus-containing phenolic resin: XZ92741 produced by Dow, solid content 56-58%, viscosity 500-2500mPa.s / 25℃, phosphorus content 9-10%;
[0219] Tetrafunctional phenolic epoxy resin: NPPN431A70 produced by Kunshan Nan Ya, solid content 70%, epoxy equivalent 200-220g / eq, softening point: 82-92℃;
[0220] PM: propylene glycol methyl ether;
[0221] EA: ethyl acetate;
[0222] IPA: isopropyl alcohol;
[0223] Spherical alumina: SLA-5, D50 particle size is 5±1μm, D90 particle size is 15±3μm;
[0224] Aluminum hydroxide: MARTINAL® OL-104LEO, purity ≥99.6%, whiteness ≥93, particle size range: D50, 1.9±0.2μm; D90, 3.2±1.0μm; oil absorption rate: 27-32 ml / 100g; conductivity (10%, in water): 20μS / cm;
[0225] GEBR573K70 resin: purchased from Hongchang Electronic Materials Co., Ltd.;
[0226] YN3570K70 resin: purchased from Jiangsu Yangnong Jinhu Chemical Co., Ltd.;
[0227] 2-Methylimidazole: Its chemical name is 2-Methylimidezale, abbreviated as 2-MI.
[0228] The solid bisphenol A epoxy resin is medium molecular weight NPES-904H produced by Kunshan Nan Ya. Performance parameters: epoxy equivalent 840-900g / eq, softening point (25℃) 100-112, melt viscosity (150℃) 6000-9000mPa・s, density (25℃): 1.18 g / cm 3 .
[0229] The MDI modified epoxy resin is DFE205 produced by Sichuan Dongcai, with a solid content of 75% and an epoxy equivalent of 250-310.
[0230] Linear bisphenol A formaldehyde resin: SH-2130 produced by Shengquan Group, hydroxyl equivalent 120-124 g / eq, free bisphenol A 13-17%, softening point 127-132℃, conductivity ≤20μs / cm.
[0231] Magnesium hydroxide: purity ≥95%, whiteness ≥92, particle size range: D50, 4±1μm; conductivity (10%, in water): 40μs / cm.
[0232] Silicon dioxide: purity ≥99.5%, whiteness ≥90, particle size range: D50, 5±1μm; conductivity (10%, in water): 40μs / cm.
[0233] Talc: SiO 2 Content 57-63, MgO content 27-33, whiteness ≥95, particle size range: D50, 3±1μm; metal impurity content ≤0.025%.
[0234] Gel time test method:
[0235] (1) Crumble the resin of the prepreg into resin powder and place it on clean kraft paper.
[0236] (2) Collect the powder and place it through a 100-mesh sieve to sift out the fine powder, not less than 200 mg.
[0237] (3) Start the gel time tester and stabilize the temperature between the hot plates at 171±2℃.
[0238] (4) Clean the hot plate, use a small spoon to take 85~100 mg of powder and put it into the hot plate, and start the timer at the same time. When the gel system reaches 10 seconds, use a toothpick to stir it evenly. After a certain period of time, gently pull the sample. If the sample breaks, stop the timer. The timer reading at this time is the gel time.
[0239] Test method for resin fluidity:
[0240] (1) Cut four (4 ± 0.02) inch × (4 ± 0.02) inch square specimens on a square die punch. The specimens should be cut 3 mm away from the edge of the material.
[0241] (2) Use an electronic balance to weigh the total weight W1 of the four samples to an accuracy of 0.01g.
[0242] (3) Stack the four specimens neatly and sandwich them between two release films.
[0243] (4) The sandwich consisting of the sample, release film and steel plate is placed in a flow press to press the laminate.
[0244] (5) Pressing parameters are: temperature 171±5℃, pressure 0.45±0.03MPa, setting time 7min.
[0245] (6) Take out the pressed laminate and remove the release film.
[0246] (7) Use a round die punch to punch a disc with a diameter of 3.192 ± 0.02 inches in the center of the laminate.
[0247] (8) Use an electronic balance to weigh the disc, W2.
[0248] (9) Calculation: Fluidity (%) = [(W1-W2×2) / W1] × 100%.
[0249] Testing method for volatile matter content:
[0250] (1) On a square die punch, cut square specimens of (4 ± 0.02) inches × (4 ± 0.02) inches or (101.6 mm × 101.6 mm) (three pieces from the left, middle, and right sides of each specimen). Punch a small hole with a diameter of about 1 / 8 mm in the corner of the specimen. The specimen cannot be cut within 10 mm from the edge of the material.
[0251] (2) Weigh the sample to an accuracy of 0.001 g and record the weight W1.
[0252] (3) Use a paper clip to pass through the small hole of the sample and hang it under the shelf of the oven.
[0253] (4) Place the rack with the sample in an oven at 163±4℃ for 15±1min.
[0254] (5) Take the sample out of the oven and weigh it within 2 minutes to an accuracy of 0.001 g, and record the weight W2.
[0255] (6) Calculate the volatile matter content (%) = [(W1-W2) / W1] × 100%.
[0256] The detection method of comparative tracking index is: the highest voltage value that the material surface can withstand 50 drops of electrolyte without forming leakage traces.
[0257] The test method for thermal conductivity (thermal conductivity) is: ASTM D5470.
[0258] The test method for peel strength is: DIN 53273.
[0259] The method for detecting bow / warpage is to ensure that the four corners of the copper clad board are completely in contact with the plane. Then, measure the distance between the highest point in the middle and the plane. The calculation formula is: Warpage = (highest point distance / PCB board long side length) * 100%.
[0260] The testing method for glass transition temperature (Tg) is: E2 / 105 DSCIPC-TM-650 2.4.25.
[0261] The detection method of thermal decomposition temperature (Td) is: 10C / min, N, 5%WtLoss.
[0262] The test method for chemical resistance (process solvent immersion method) is: no fading for 60 minutes.
[0263] The detection method for antimony and halogen content is: IEC61249-2-21.
[0264] The detection method of DMF content is: referring to US EPA 8270D:2014 method and using CC-MS for analysis.
[0265] Example 1
[0266] The raw material formula of the adhesive solution for halogen-free and antimony-free flame retardant laminate (FR-4.1) is shown in Table 1.
[0267] Table 1 Raw material formula
[0268]
[0269] Note: Mixed solvent 1 refers to: DMF (N,N-dimethylformamide), ethanol, dimethyl sulfoxide (DMSO), and γ-butyrolactone (GBL) mixed in a mass ratio of 5:3:1:1;
[0270] The mixed solvent 2 is a mixture of PM (propylene glycol methyl ether), ethyl acetate and isopropanol in a mass ratio of 5:3:2.
[0271] The method for manufacturing the adhesive solution of the halogen-free and antimony-free flame-retardant laminate (FR-4.1) specifically comprises the following steps:
[0272] (1) Mix the mixed solvent 1 (added according to each component), the curing agent (added according to each component), the curing accelerator and the flame retardant, and stir until dissolved for 10-12 hours to obtain a mixture A;
[0273] (2) Mixing the mixture A with the silane coupling agent, the resin (added according to each component), and the mixed solvent 2 (added according to each component), and stirring for 1-2 hours to obtain a mixture B;
[0274] (3) Under stirring conditions, the mixture B and the inorganic filler (added according to each component) are mixed, and shear-ripened at a speed of 2200 rpm and a temperature of 50° C. for 5 hours, and then shear-ripened at a speed of 1100 rpm and a temperature of 50° C. for 7 hours (total aging time of about 12 hours), and finally a halogen-free and antimony-free flame-retardant laminate adhesive is obtained. Under the condition of a total aging time of about 12 hours, the gel time of the adhesive is 250-260 s.
[0275] When observing mixture A under a polarizing microscope at 40x (total magnification), there were less than 3 DICY crystals in any field of view.
[0276] Example 2
[0277] This embodiment provides a method for preparing a prepreg for a halogen-free and antimony-free flame-retardant laminate (FR-4.1), which comprises the following steps:
[0278] The electronic grade glass fiber cloth is coated with the adhesive solution described in Example 1, and then dried to obtain the product.
[0279] The electronic grade glass cloth (alkali-free glass fiber cloth for printed circuit boards) is a prepreg raw material conventionally used in the art, such as electronic grade glass cloth 7628 or electronic grade glass cloth 2116.
[0280] In the method for preparing the prepreg for the halogen-free and antimony-free flame-retardant laminate (FR-4.1), the coating equipment is a vertical glue coating machine.
[0281] (1) Prepreg produced from electronic grade glass cloth 7628:
[0282] The coating vehicle speed was 17 m / min.
[0283] The drying temperature is 210°C.
[0284] The temperature of the glue solution is 40°C.
[0285] The mass content of the resin in the prepreg can reach 45%.
[0286] The gel time of the prepreg can reach 90-100 s (the gel time of the glue solution can reach 250-260 s).
[0287] The fluidity of the prepreg can reach 20-28%.
[0288] The volatile matter of the prepreg is ≤0.5%.
[0289] (2) Prepreg produced from electronic grade glass cloth 2116:
[0290] The coating vehicle speed was 16 m / min.
[0291] The drying temperature is 215°C.
[0292] The temperature of the glue solution is 40°C.
[0293] The mass content of the resin in the prepreg is 55-56%.
[0294] The gel time of the prepreg can reach 85-95 s (the gel time of the glue solution can reach 250-260 s).
[0295] The fluidity of the prepreg can reach 26-32%.
[0296] The volatile matter of the prepreg is ≤0.5%.
[0297] Example 3
[0298] This embodiment provides a method for preparing a halogen-free and antimony-free flame-retardant laminate (FR-4.1), which comprises the following steps:
[0299] Lamination: 8 sheets of prepregs (1*2116+6*7628+1*2116) prepared in Example 2 are stacked and covered with copper foil on both the upper and lower surfaces to obtain a semi-finished plate. The semi-finished product is formed by 8 prepregs in the middle, upper and lower copper foils, upper and lower steel plates, and 18 pieces of kraft paper on the upper and lower surfaces;
[0300] ② The semi-finished product is subjected to hot-pressing and vacuum pressing to obtain.
[0301] No pressure is required when stacking. Stacking requires following four principles: the principle of matching high and low glue content, the principle of consistent layout, the principle of structural symmetry, and the principle of left and right matching.
[0302] In step ②, the pressing method is hot pressing and vacuum segmented pressing. Ensure that the plate is cooled gradually to avoid direct pressure release after hot pressing, which will cause large internal stress of the plate, and increase cold pressing to reduce plate warping.
[0303] The hot pressing vacuum value is 750 mmHg.
[0304] Stage 1: Start to evacuate until the hot pressing vacuum value reaches 750 mmHg, and maintain it at 740-750 mmHg. Hot pressing temperature: 120-210℃ (this temperature range indicates a linear increase from 120℃ to 210℃), hot pressing pressure: 5-25 kg / cm 2 (This pressure range represents from 5 kg / cm 2 Linear pressure increase to 25 kg / cm 2 ), hot pressing time: 55min. The heating and pressure increase are completed during the entire pressing process, that is, the pressure increase and heating time is 55min, the starting temperature of the hot pressing is 120℃, and the hot pressing pressure is 5 kg / cm 2 The hot pressing end point temperature is 210℃ and the hot pressing pressure is 25 kg / cm 2 That is, the heating rate of hot pressing is 1.63℃ / min, and the pressure increase rate of hot pressing is 0.36 kg / cm 2 / min.
[0305] Stage 2: Continuously evacuate to ensure that the hot pressing vacuum value is 740-750 mmHg, hot pressing temperature: 210℃, hot pressing pressure is divided into initial pressure, mid-term pressure and late pressure, among which: initial pressure is 25kg / cm 2 , hot pressing time is 10min, medium pressure is 35kg / cm 2 The hot pressing time is 35 minutes, and the later pressure is 20 kg / cm 2 , Hot pressing time: 15min.
[0306] Stage 3: Stop vacuuming, hot pressing temperature: 210-120℃ (this temperature range represents a linear temperature drop from 210℃ to 120℃), hot pressing pressure: 20-30 kg / cm 2 (This pressure range represents from 20 kg / cm 2 Linear pressure increase to 30 kg / cm 2 ), hot pressing time: 30min. Cooling and pressing are completed during the whole pressing process, that is, the time of pressing and cooling is 30min, the starting temperature of hot pressing is 210℃, and the hot pressing pressure is 20 kg / cm 2 The hot pressing end point temperature is 120℃ and the hot pressing pressure is 30 kg / cm 2That is, the cooling rate of hot pressing is 3.00℃ / min, and the pressure increase rate of hot pressing is 0.33 kg / cm 2 / min.
[0307] Comparative Example 1
[0308] The mixed solvent 1 in Example 1 was replaced with 500 parts of DMF (single solvent), and the other conditions were the same as those in Example 1. The method for preparing the glue solution was the same as that in Example 1.
[0309] The resin in Table 1 was not dissolved uniformly and fully; moreover, under the condition of a total aging time of about 12 hours, the gel time of the glue solution was 300-320 s, which was significantly prolonged.
[0310] The DMF content of the copper clad laminate prepared in this comparative example exceeds the standard, and the DMF content in the copper clad laminate product is 10000-20000ppm.
[0311] Comparative Example 2
[0312] (1) The mixed solvent 1 in Example 1 was replaced with 600 parts of DMF (single solvent), and the other conditions were the same as those in Example 1. The method for preparing the glue solution was the same as that in Example 1. Under the condition that the total aging time was about 12 hours, the gel time of the glue solution was 250-260 seconds.
[0313] (2) The preparation method of the prepreg for the halogen-free and antimony-free flame-retardant laminate (FR-4.1) in Comparative Example 2 is the same as that in Example 2.
[0314] (3) The preparation method of the halogen-free and antimony-free flame-retardant laminate (FR-4.1) in Comparative Example 2 is the same as that in Example 3.
[0315] (4) The copper clad laminate obtained in step (3) is subjected to performance measurement.
[0316] The DMF content of the copper clad laminate prepared in this comparative example exceeds the standard, and the DMF content in the copper clad laminate product is 15000-25000ppm.
[0317] Comparative Example 3
[0318] The mixed solvent 1 in Example 1 was replaced with 500 parts of acetone (single solvent), and the other conditions were the same as those in Example 1. The method for preparing the glue solution was the same as that in Example 1.
[0319] Observe the mixture A in step (1) under a polarizing microscope at 40 times (total magnification), and there are 10-20 DICY crystals. If there are less than 3 DICY crystals in any field of view, it is necessary to extend the mixing time by 1-2 hours or increase the amount of acetone solvent by 5%, that is, 525 parts of acetone (single solvent).
[0320] The gel time of the glue in step (3) is 330-350 s, which is significantly extended. If the aging reaction is to meet the standard, the total aging time is about 12 hours, the gel time of the glue is 250-260 s, and the amount of solvent needs to be increased by 100%, that is, 1000 parts of acetone (single solvent).
[0321] Comparative Example 4
[0322] The mixed solvent 1 in Example 1 was replaced with 500 parts of the mixed solvent 3, wherein the mixed solvent 3 was obtained by mixing DMF (N,N-dimethylformamide), acetone and butanone in a mass ratio of 5:3:2, and other conditions were the same as those in Example 1. The method for preparing the glue solution was the same as that in Example 1.
[0323] The resin in Table 1 is not dissolved uniformly and fully; moreover, under the condition of a total aging time of about 12 hours, the gel time of the glue solution in step (3) is 320-340 s, which is significantly prolonged.
[0324] Comparative Example 5
[0325] The mixed solvent 2 in Example 1 was replaced with 150 parts of the mixed solvent 4, wherein the mixed solvent 4 was obtained by mixing acetone, ethyl acetate and isopropanol in a mass ratio of 5:3:2, and other conditions were the same as those in Example 1. The method for preparing the adhesive solution was the same as that in Example 1.
[0326] The gel time of the glue in step (3) is 320-340 s, which is significantly extended. If the aging reaction is to meet the standard, the gel time of the glue is 250-260 s under the condition of a total aging time of about 12 hours, and the amount of solvent needs to be increased by 30%, that is, 195 parts of mixed solvent 4.
[0327] Example 4
[0328] The raw material formula of the halogen-free and antimony-free flame-retardant laminate (CEM-3, among which the PP (semi-cured sheet) produced by electronic glass fiber felt requires this glue) is as follows.
[0329] Table 2
[0330]
[0331] Note: Mixed solvent A refers to: N,N-dimethylformamide DMF, ethanol, dimethyl sulfoxide DMSO, and γ-butyrolactone GBL mixed in a mass ratio of 5:3:1:1;
[0332] The mixed solvent B is obtained by mixing propylene glycol methyl ether PM, ethyl acetate EA and isopropanol in a mass ratio of 5:3:2.
[0333] The preparation method of the adhesive for halogen-free and antimony-free flame-retardant laminate (CEM-3, in which the PP (semi-cured sheet) produced by electronic glass fiber felt needs to use this adhesive) specifically includes the following steps:
[0334] (1) Mix the mixed solvent 1 (added according to each component), the curing agent (added according to each component), and the curing accelerator, and stir until dissolved for 10-12 hours to obtain a mixture A;
[0335] (2) Mixing the mixture A with the silane coupling agent, the resin (added according to each component), and the mixed solvent 2 (added according to each component), and stirring for 1-2 hours to obtain a mixture B;
[0336] (3) Under stirring conditions, the mixture B and the inorganic filler (added according to each component) are mixed, and shear-ripened at a speed of 1500 rpm and a glue temperature of 45° C. for 6 hours, and then shear-ripened at a speed of 1000 rpm and a glue temperature of 45° C. for 14 hours (total aging time is about 20 hours), and finally, the glue for halogen-free and antimony-free flame-retardant electronic glass fiber felt is obtained.
[0337] Example 5
[0338] The present embodiment provides a method for preparing a prepreg for a halogen-free and antimony-free flame-retardant laminate (CEM-3), which comprises the following steps:
[0339] The electronic glass fiber felt is coated with the glue in Example 4 and then dried to obtain the electronic glass fiber felt.
[0340] Among them, the electronic glass fiber felt is a product type purchased from Jiangsu Changhai Electronic Glass Fiber Felt: EMP-75A1 or EMP-105A1 (alkali metal content is not more than 0.8%), and its parameter indicators are shown in the following table.
[0341] Table 3
[0342]
[0343] Among them, the specific parameters of the prepreg produced from electronic grade glass fiber mat are:
[0344] The coating equipment is a horizontal glue coating machine, and the coating speed is 10m / min. The drying temperature is 220℃. The temperature of the glue solution is 35℃. The mass content of the resin in the prepreg can reach 85%. The fluidity of the prepreg can reach 25~30%. The volatile matter of the prepreg is ≤0.5%.
[0345] Example 6
[0346] This embodiment provides a method for preparing a halogen-free and antimony-free flame-retardant laminate (CEM-3), which comprises the following steps:
[0347] (1) Lamination: 4 prepregs (1*7628+2*EMP-105A1+1*7628) are stacked and covered with copper foil on both the upper and lower surfaces to obtain a semi-finished plate. The semi-finished product is formed by 4 prepregs in the middle, upper and lower copper foils, upper and lower steel plates, and 18 pieces of kraft paper on the upper and lower surfaces;
[0348] Among them, the 4 stacked prepregs are: 1 prepreg produced by electronic grade glass cloth 7628 + 2 prepregs produced by electronic grade glass fiber felt EMP-105A1 prepared in Example 5 + 1 prepreg produced by electronic grade glass cloth 7628.
[0349] Electronic grade glass cloth 7628 (purchased from Taishan Fiberglass, weight: 210g / m 2 ) The preparation method of the prepreg produced comprises the following steps:
[0350] Apply glue on electronic grade glass fiber cloth 7628 and then dry it. The coating equipment is a vertical glue machine, and the coating speed is 19m / min. The drying temperature is 210℃. The temperature of the glue is 40℃. The mass content of the resin in the prepreg can reach 50%. The gel time of the prepreg can reach 100-110s. The formula of the glue applied on the electronic grade glass fiber cloth 7628 is shown in the following table.
[0351] Table 4 Raw material formula
[0352]
[0353] Note: Mixed solvent 1 refers to: N,N-dimethylformamide DMF, ethanol, dimethyl sulfoxide DMSO, and γ-butyrolactone GBL mixed in a mass ratio of 5:3:1:1;
[0354] The mixed solvent 2 is obtained by mixing propylene glycol methyl ether PM, ethyl acetate EA and isopropanol in a mass ratio of 5:3:2.
[0355] The preparation method of coating glue on electronic grade glass fiber cloth 7628 specifically includes the following steps:
[0356] ① Mix the mixed solvent A (added according to each component), curing agent (added according to each component), curing accelerator and flame retardant, and stir until dissolved for 10-12 hours to obtain mixture A;
[0357] ② Mix mixture A with silane coupling agent, resin (added according to each component), and mixed solvent B (added according to each component), and stir for 1-2 hours to obtain mixture B;
[0358] ③ Under stirring conditions, mix mixture B and inorganic filler (added according to each component), first shear and mature at a speed of 2200rpm and a glue temperature of 50℃ for 5 hours, then shear and mature at a speed of 1100rpm and a glue temperature of 50℃ for 7 hours (total aging time is about 12 hours), and finally obtain the electronic grade glass fiber cloth 7628 coated with glue.
[0359] (2) The semi-finished product is subjected to hot pressing and vacuum pressing to obtain the product.
[0360] No pressure is required when stacking. Stacking requires the electronic glass fiber cloth PP to be on the outer layer and the electronic glass fiber felt to be in the core.
[0361] In step (2), the pressing method adopts hot pressing vacuum segmented pressing (the hot pressing vacuum value is 750 mmHg). Ensure that the plate is cooled gradually to avoid direct pressure release after hot pressing, which will cause large internal stress of the plate, and increase cold pressing to reduce plate warping.
[0362] Stage 1: Start to evacuate until the hot pressing vacuum value reaches 750 mmHg, and maintain it at 740-750 mmHg. Hot pressing temperature: 120-210℃ (this temperature range indicates a linear increase from 120℃ to 210℃), hot pressing pressure: 5-25 kg / cm 2 (This pressure range represents from 5 kg / cm 2 Linear pressure increase to 25 kg / cm 2 ), hot pressing time: 55min. The heating and pressure increase are completed during the entire pressing process, that is, the pressure increase and heating time is 55min, the starting temperature of the hot pressing is 120℃, and the hot pressing pressure is 5 kg / cm 2 The hot pressing end point temperature is 210℃ and the hot pressing pressure is 25 kg / cm 2 That is, the heating rate of hot pressing is 1.63℃ / min, and the pressure increase rate of hot pressing is 0.36 kg / cm 2 / min.
[0363] Stage 2: Continuously evacuate to ensure that the hot pressing vacuum value is 740-750 mmHg, hot pressing temperature: 210℃, hot pressing pressure is divided into initial pressure, mid-term pressure and late pressure, among which: initial pressure is 25kg / cm 2 , hot pressing time is 10min, medium pressure is 35kg / cm 2 The hot pressing time is 35 minutes, and the later pressure is 20 kg / cm 2 , Hot pressing time: 15min.
[0364] Stage 3: Stop vacuuming, hot pressing temperature: 210-120℃ (this temperature range represents a linear temperature drop from 210℃ to 120℃), hot pressing pressure: 20-30 kg / cm 2 (This pressure range represents from 20 kg / cm 2 Linear pressure increase to 30 kg / cm 2 ), hot pressing time: 30min. Cooling and pressing are completed during the whole pressing process, that is, the time of pressing and cooling is 30min, the starting temperature of hot pressing is 210℃, and the hot pressing pressure is 20 kg / cm 2 The hot pressing end point temperature is 120℃ and the hot pressing pressure is 30 kg / cm 2 That is, the cooling rate of hot pressing is 3.00℃ / min, and the pressure increase rate of hot pressing is 0.33 kg / cm 2 / min.
[0365] Effect Example 1
[0366] The copper clad laminate obtained in Example 3 was subjected to performance testing, and the results are shown in Table 5.
[0367] Table 5 Performance parameters of copper clad laminate in Example 3
[0368]
[0369] Effect Example 2
[0370] The performance of the laminate obtained in Example 6 was measured and the results are shown in Table 6.
[0371] Table 6 Performance parameters of the laminate in Example 6
[0372]
[0373] Effect Example 3
[0374] The properties of the laminates obtained in Comparative Examples 1-5 were measured, and the results are shown in Table 7.
[0375] Table 7 Performance parameters of laminates in Comparative Examples 1-5
[0376]
[0377] From Table 5, Table 6 and Table 7, we can see that:
[0378] (1) The flame-retardant laminate (FR-4.1 or CEM-3) with high thermal conductivity, CTI ≥ 600 V, TG ≥ 155°C, and halogen-free and antimony-free prepared by the mixed solvent of the present invention in Examples 3 and 6 meets the production process requirements of the downstream printed circuit board (PCB) for the board, and the DMF content of the prepared board can be less than 500ppm. In addition, the board has good comprehensive properties, especially halogen-free, thermal conductivity, CTI, flame retardancy, TG, thickness uniformity, high thermal conductivity, no delamination, no blistering in the thermal stress test.
[0379] (2) In Comparative Examples 1-5, the mixed solvent of the present invention is not used. Either the DMF content exceeds the standard (as shown in Comparative Examples 1 and 2), or the performance of the laminate deteriorates, for example, the tracking index is reduced and the glass transition temperature is reduced (as shown in Comparative Examples 3-5).
Claims
1. A mixed solvent for preparing a glue solution for halogen-free and antimony-free flame-retardant laminates, characterized in that: The mixed solvent comprises mixed solvent 1 and mixed solvent 2; wherein: The mixed solvent 1 comprises: N,N-dimethylformamide, ethanol, dimethyl sulfoxide, and γ-butyrolactone, and the mass ratio of the N,N-dimethylformamide, the ethanol, the dimethyl sulfoxide, and the γ-butyrolactone is (4-6): (2-4): 1:1; The mixed solvent 2 comprises: propylene glycol methyl ether, ethyl acetate, and isopropanol, and the mass ratio of the propylene glycol methyl ether, the ethyl acetate, and the isopropanol is (4-6): (2-4):
2.
2. The mixed solvent according to claim 1, characterized in that The mixed solvent meets one or more of the following conditions: (1) In the mixed solvent 1, the mass ratio of the N,N-dimethylformamide, the ethanol, the dimethyl sulfoxide, and the γ-butyrolactone is 5:3:1:1; (2) In the mixed solvent 2, the mass ratio of the propylene glycol methyl ether, the ethyl acetate and the isopropanol is 5:3:2; (3) The mass fraction of the mixed solvent 1 is 450-550 parts, for example, 500 parts; (4) The mass fraction of the mixed solvent 2 is 135-165 parts, for example, 150 parts; Alternatively, the mass fraction of the mixed solvent 2 is 765-935 parts, for example 850 parts.
3. A method for preparing a halogen-free and antimony-free flame-retardant adhesive for laminated boards, characterized in that: The raw materials of the glue solution include the following components by mass: Resin, curing agent, curing accelerator, silane coupling agent, and the mixed solvent according to claim 1 or 2; Optionally, the raw material further comprises an inorganic filler; The preparation method of the adhesive for the halogen-free and antimony-free flame-retardant laminate comprises the following steps: (1) Mixing the mixed solvent 1, the curing agent, the curing accelerator and a portion of the inorganic filler in the mixed solvent, and stirring until dissolved to obtain a mixture A; (2) mixing the mixture A with the silane coupling agent, the resin, and the mixed solvent 2 in the mixed solvent, and stirring to obtain a mixture B; (3) Under stirring conditions, the mixture B and the remaining part of the inorganic filler are mixed, and sheared and ripened to obtain the halogen-free and antimony-free flame-retardant laminate adhesive.
4. The method for preparing the adhesive solution for halogen-free and antimony-free flame-retardant laminated boards according to claim 3, characterized in that: The raw materials of the glue solution include the following component A: (1) 360-440 parts of bisphenol A epoxy resin, wherein the bisphenol A epoxy resin has an epoxy equivalent of 185-190 g / eq and a viscosity of 12000-15000 mPa·s at 25° C.; 1260-1540 parts of a DOPO type modified phosphorus-containing epoxy resin, wherein the DOPO type modified phosphorus-containing epoxy resin has an epoxy equivalent of 295-335 g / eq; 180-220 parts of bisphenol A novolac epoxy resin, wherein the epoxy equivalent of the bisphenol A novolac epoxy resin is 190-220 g / eq; 90-110 parts of a novolac epoxy resin, wherein the novolac epoxy resin has an epoxy equivalent of 176-181 g / eq; 270-330 parts of bisphenol A type phosphorus-containing phenolic resin, wherein the viscosity of the bisphenol A type phosphorus-containing phenolic resin at 25° C. is 500-2500 mPa.s; 90-110 parts of a tetrafunctional novolac epoxy resin, wherein the epoxy equivalent of the tetrafunctional novolac epoxy resin is 200-220 g / eq; 450-550 parts of the mixed solvent 1, 135-165 parts of the mixed solvent 2; 72-88 parts of curing agent; 0.5-1.5 parts of curing accelerator; 18-22 parts of silane coupling agent; Optionally, the raw material A further comprises an inorganic filler.
5. The method for preparing the adhesive for halogen-free and antimony-free flame-retardant laminated board according to claim 3, characterized in that: The raw materials of the glue solution include the following component B: 540-660 parts of bisphenol A epoxy resin, wherein the bisphenol A epoxy resin has an epoxy equivalent of 185-190 g / eq and a viscosity of 12000-15000 mPa·s at 25° C.; 900-1100 parts of DOPO type modified phosphorus-containing epoxy resin, wherein the epoxy equivalent of the DOPO type modified phosphorus-containing epoxy resin is 295-335 g / eq; 360-440 parts of solid bisphenol A epoxy resin, wherein the solid bisphenol A epoxy resin has an epoxy equivalent of 840-900 g / eq and a melt viscosity of 6000-9000 mPa·s at 150° C.; 180-220 parts of MDI modified epoxy resin, wherein the epoxy equivalent of the MDI modified epoxy resin is 250-310 g / eq; and, 450-550 parts of a linear bisphenol A formaldehyde resin, wherein the linear bisphenol A formaldehyde resin has a hydroxyl equivalent of 120-124 g / eq; 450-550 parts of the mixed solvent 1, 765-935 parts of the mixed solvent 2; 72-88 parts of curing agent; 0.9-1.1 parts of curing accelerator; 18-22 parts of a silane coupling agent; and, Inorganic filler.
6. A halogen-free and antimony-free flame-retardant adhesive for laminated boards, characterized in that: The invention is prepared by the method for preparing the adhesive for halogen-free and antimony-free flame-retardant laminated boards as described in any one of claims 3 to 5.
7. A method for preparing a prepreg for a halogen-free and antimony-free flame-retardant laminate, characterized in that: The method comprises the following steps: coating the adhesive solution as claimed in claim 6 on the reinforcing material, and drying the reinforced material.
8. A prepreg for a halogen-free and antimony-free flame-retardant laminate, characterized in that: The semi-cured sheet is prepared by the method for preparing the halogen-free and antimony-free flame-retardant laminate according to claim 7.
9. A halogen-free and antimony-free flame-retardant laminate, characterized in that: The halogen-free and antimony-free flame-retardant laminate comprises at least one prepreg for the halogen-free and antimony-free flame-retardant laminate and a metal foil or a release film covering one side or both sides of the laminated prepreg.
10. A method for preparing the halogen-free and antimony-free flame-retardant laminate according to claim 9, comprising the following steps: Lamination: Laminating a plurality of halogen-free and antimony-free flame-retardant laminates as claimed in claim 9 with prepregs, and covering the upper and lower surfaces with metal foil or release film to obtain a semi-finished plate; ② The semi-finished plate is subjected to hot pressing and vacuum pressing to obtain the semi-finished plate.